Analisis Pekerjaan Ibu Hamil yang Berkaitan dengan Pestisida terhadap Kejadian Stunting di Nagari Sungai Nanam, Kecamatan Lembah Gumanti Kabupaten Solok - Kurniati Kurniati; Indang Dewata; Skunda Diliarosta; Elsa Yuniarti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Stunting is defined by the World Health Organization (WHO) as growth and development abnormalities in children. According to SSGI 2021 data, the Solok district had the highest stunting rate in West Sumatra Province when compared to other urban districts in 2021, with the highest prevalence of stunting being in the working area of the Alahan Panjang Health Center, with 536 cases (37.04%) located in Nagari Sungai Nanam, Lembah Gumanti District, Solok Regency. This research is descriptive, with a qualitative methodology and a cross-sectional design. The population consisted of all pregnant mothers in Nagari Sungai Nanam, Lembah Gumanti District, Solok Regency, with 28 persons chosen randomly (random purposive selection) from 14 jorongs in Nagari Sungai Nanam, Lembah Gumanti District, Solok Regency. The data were gathered through observation, interviews, and documentation using questionnaires. Data were processed using SPSS version 25 with univariate tests, analyzed descriptively, and presented in tabular form. The findings revealed that 20 pregnant women (71.43%) in Nagari Sungai Nanam, Lembah Gumanti District, and Solok Regency were still participating in the agricultural process, from pesticide preparation to agricultural product harvesting. This is due to economic pressures as well as a lack of knowledge.